Development’s Denial of Social Justice - Blunt, Peter; Lindroth, Henrik (Taylor and Francis, 2013)
Resistance to criticism in the field of development has prevented systemic change and has led to a denial of social justice. This has been a function of the language of development; establishment control over forms of critical discourse; selective crises reportage; and normal scientific behavior. Following Popper (1970), these defenses should be lowered so that bold alternative conjectures concerning social injustice can be set against prevailing orthodoxies. The work of Arundhati Roy is used to help make this case, and it is suggested that the search for alternatives needs to extend beyond the architects and agents of the neoliberal paradigm.